Modelos chuva-vazão para o Ribeirão Cambezinho em Londrina - PR - Ramos, Lucas Mancini (2013)
The urban development of a city implies increasing soil sealing and consequently increase the risk of flooding. The objective of this paper is estimated flood hydrographs of stream Cambezinho located in Londrina-PR. These estimates were made for rainfall-runoff models with adoption scenario that regarding the urbanization process in order to determine the risk of flooding. To estimate the hydrograph were considered the following methods: computational method with free program (PIHMgis) and traditional methods (Soil Conservation Service, Snyder and infiltration with index Φ). GIS technology was applied to obtain the parameters involved in these methods. The flow of the project were estimated for return periods of 5, 10, 25, 50 and 100 years. The values found by computational methodology were considered more appropriate to the scenarios used when purchased with other methodologies, as approaching values obtained experimentally.